Studying nursing at Australian satellite university campuses: A review of teaching, learning and support. (13th May 2021) - Hays, Catherine; Devine, Susan; Wongtongkam, Nualnong; Glass, Beverley
Abstract: Distribution of the Australian health workforce is uneven, with the majority of health professionals favouring metropolitan areas over rural and remote regions. Although nurses account for the largest proportion of the Australian rural and remote health workforce, difficulties with staff recruitment and retention can impact the health care outcomes of these vulnerable populations. Satellite university campuses that offer undergraduate nursing programs might therefore contribute to a more sustainable rural and remote nursing workforce. This narrative literature review aimed at investigating the barriers and enablers that affect students enrolled at satellite nursing campuses, education delivery methods and academic and non‐academic strategies employed to enhance the student learning experience. The literature was reviewed across 6 health and education databases. After screening, 12 articles met the inclusion criteria and were analysed, and the data were synthesised using a thematic approach. Three themes arose from the review: student characteristics and associated barriers and enablers to studying nursing at a satellite campus; teaching strategies and learning experiences; and academic and pastoral support. Students studying at satellite campuses were found to have different education experiences and faced challenges unique to their context; however, home support networks and small class sizes were seen as enabling factors. Education delivery methods and support strategies varied depending on remoteness and resources available. Consideration of the factors that affect satellite campus nursing students has the potential to increase student satisfaction and retention, which could result in a more sustainable rural and remote nursing workforce.